CONSUMER’S PERCEIVED VALUE AND BUYING BEHAVIOR OF STORE BRANDS: AN EMPIRICAL INVESTIGATION - Nugroho, Wahyu Adhi; Wihandoyo, Luki Safitri (Journal of Business Strategy and Execution, 2009)
Buying processes in grocery shopping involve many factors relating to the final decision of the consumers and those aspects influence Consumer Perceived Value and their buying behavior on deciding which type of product they would buy. Store brands existence as an option in today modern grocery shopping have an important position in retail strategy nowadays and the role have increased during the development of modern grocery stores in Indonesia. Therefore, understanding store brand buyer behavior is an essential topic for marketers and researchers. Demographic Profiling, Mean Value Analysis, Crosstabs Analysis, Reliability Analysis, Factor Analysis – Principal Component Analysis (Varimax Method), Multiple Linear Regression are used in this research. Dominating, significant variables revealed, pattern of relationship showed. In overall, the findings shows that consumer’s perceived value contribute positively to their perceptions of store brands and the better knowledge on the aspects of store brand products due to their past experience in purchasing the items lead to positive perceptions which eventually will lead to good possibility for them in re-purchasing store brands products in the future.